A short review and preliminary study on peanut (Arachis hypogaea L.) tissue culture - Nahreen, Ashfia (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.